Investigation of the forensic GlobalFiler loci in the genetically isolated Circassian subpopulation in Jordan - AL-Eitan, Laith N.; Darwish, Nizar N.; Hakooz, Nancy M.; Dajani, Rana B. (Gene, 2020)
•GlobalFiler STR loci were used to genotype Jordanian Circassians for the first time.•Allele frequencies and forensic efficiency parameters of the 21 autosomal STR were determined.•The SE33 locus exhibited the highest PIC value (93%).•The TPOX locus (54%) was the least informative.•The Combined match probability for the 21 autosomal STR loci is 5.02E-24. Circassians are a Caucasian ethnic group who make up a significant minority in Jordan. Although other ethnic groups have been the subject of forensic genetic analysis, no published study has investigated the forensic genetic efficiency of short tandem repeats (STRs) in Circassians, neither in Jordan nor in any other country. The main objective of the current study is to determine the allelic frequencies and evaluate the forensic efficiency parameters of 21 highly polymorphic autosomal STR loci among the Circassian subpopulation in Jordan. The GlobalFiler loci were amplified using DNA extracted from the whole blood samples of 150 Jordanian Circassians. The SE33 locus was found to be the most informative and polymorphic STR marker while TPOX was the least informative. However, allele 8 of TPOX was the most common across all of the investigated 21 loci in Jordanian Circassians. The combined matching probability (CMP) and combined power of discrimination (CPD) were 5.02E-24 and 0.9999999, respectively.